Involvement of sweet pepper CaLOX2 in jasmonate‐dependent induced defence against Western flower thrips. Issue 10 (27th February 2019) - Sarde, Sandeep J; Bouwmeester, Klaas; Venegas‐Molina, Jhon; David, Anja; Boland, Wilhelm; Dicke, Marcel
Abstract: Insect herbivory can seriously hinder plant performance and reduce crop yield. Thrips are minute cell‐content‐feeding insects that are important vectors of viral plant pathogens, and are serious crop pests. We investigated the role of a sweet pepper ( Capsicum annuum ) lipoxygenase gene, CaLOX2, in the defense of pepper plants against Western flower thrips ( Frankliniella occidentalis ). This was done through a combination of in‐silico, transcriptional, behavioral and chemical analyses. Our data show that CaLOX2 is involved in jasmonic acid (JA) biosynthesis and mediates plant resistance. Expression of the JA‐related marker genes, CaLOX2 and CaPIN II, was induced by thrips feeding. Silencing of CaLOX2 in pepper plants through virus‐induced gene silencing (VIGS) resulted in low levels of CaLOX2 transcripts, as well as significant reduction in the accumulation of JA, and its derivatives, upon thrips feeding compared to control plants. CaLOX2 ‐silenced pepper plants exhibited enhanced susceptibility to thrips. This indicates that CaLOX2 mediates JA‐dependent signaling, resulting in defense against thrips. Furthermore, exogenous application of JA to pepper plants increased plant resistance to thrips, constrained thrips population development and made plants less attractive to thrips. Thus, a multidisciplinary approach shows that an intact lipoxygenase pathway mediates various components of sweet pepper defense against F. occidentalis . Abstract : Through a combination of in‐silico, transcriptional, behavioural and chemical analyses, here we demonstrate that the lipoxygenase gene, CaLOX 2, mediates jasmonate‐dependent induced defence of sweet pepper plants against Western flower thrips.